TGF-β1 and TNF-α after red blood cell transfusion in colorectal cancer patients - Milasiene, V.; Stratilatovas, E.; Characiejus, D.; Kazbariene, B.; Norkiene, V. (Experimental Oncology, 2007)
Operations in patients with cancer are associated with blood transfusion to restore normal physiology. Blood transfusion can cause the immunomodulatory effect. There is lack of the literature data about influence of blood transfusion on the blood serum levels of cytokines TGF-β and TNF-α, though these cytokines are important in neoplasia development. The aim of our study was to estimate changes in the concentration of cytokines TGF-β1 and TNF-α in colorectal cancer patients’ peripheral blood after surgery and allogenic red blood cell transfusion. Methods: Venous blood of 64 patients with colorectal adenocarcinoma in stage III was tested before and after the surgery. Concentration of cytokines TGF-β1 and TNF-α was quantitatively measured by ELISA. Results: TGF-β1 and TNF-α concentration significantly increased in the group of transfused colorectal cancer patients (before operation: TGF-β 10.1 ± 1.3 ng/ml, TNF-α 20.9 ± 1.7 pg/ml and after operation and RBC transfusion: TGF-β 15.9 ± 1.7 ng/ml; TNF-α 27.0 ± 2.1 pg/ml). Statistical analysis has shown that serum levels of cytokines didn’t change significantly after surgery in non-transfused patients group. Conclusion: These results indicate that levels of multipotent cytokines TGF-β1 and TNF-α were elevated after red blood cell (RBC) transfusion in colorectal cancer patients.